THE EFFECT OF PRODUCT QUALITY AND PRICE ON THE PURCHASE DECISION OF MYKONOS PERFUME PRODUCTS AMONG FEB UNM STUDENTS IN MAKASSAR CITY - Muh. Syahrul Ramadhan; Nurman Nurman; Isma Azis Riu; Muhammad Ichwan Musa; Rahmat Riwayat Abadi (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the effect of product quality, price, and brand image on purchase decisions of Mykonos perfume. The research adopts a quantitative approach using a survey method by distributing questionnaires to respondents who have used or are familiar with Mykonos perfume. The sampling technique used is purposive sampling, with a total of 105 respondents determined based on the Slovin formula. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that product quality has a positive and significant effect on purchase decisions. Price also has a positive and significant influence on purchase decisions, indicating that consumers consider price suitability in making purchasing decisions. In addition, brand image has a positive and significant effect on purchase decisions, suggesting that a strong brand perception can enhance consumer confidence in choosing the product. Simultaneously, product quality, price, and brand image significantly influence purchase decisions. These findings indicate that improving product quality, setting competitive prices, and strengthening brand image are important strategies to increase consumer purchase decisions.Keywords: Product Quality, Price, Brand Image, Purchase Decision, Mykonos Perfume